ANALISA TEKNIK FOTOGRAFI DALAM TREN FOOD PHOTOGRAPHY - Kadek Dede Muliawan; Sagung Intan Pradnyanita (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2021)
This research aims to solve the problems faced by most of the business actors who have just pioneered especially in the food and beverage sector, because at the time of the COVID-19 pandemic they were currently required to save production costs to save on product marketing costs due to their limited capital. have so that the sales of a product are not optimal. In this problem, in particular, their food and beverage businesses are required to have photos of the food and drinks they sell as attractive as possible to attract buyers, but most of them cannot afford to pay for the services of professional photographers to create such photos. So this research will describe starting from camera operation, some of the techniques used by professional photographers, things that need to be considered in photographing, to tips and tricks for creating good and attractive-looking photos like a professional photographer so that business people can do it themselves. this new pioneering food and beverage. In this study the authors used qualitative methods, made observations of microbusinesses that had just been formed this year, according to the target of the theory writer used are the basic theories of photography itself, but the authors summarize them so that they are shorter, concise and clear, only use the theory used to photograph the food itself to make it easier to understand, for example, camera operating techniques, lighting techniques, composition, to the introduction of various food photography moods, and others.